Empowerment of rural community through the development of renewable electricity - Dessy Rachmawatie; Ernan Rustiadi; Akhmad Fauzi; Bambang Juanda (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2020)
The purpose of this study is to analyze the empowerment of electricity beneficiaries through community empowerment activities following the use of wind and solar renewable energy (PLTH) in Pantai Baru. To achieve these objectives, the data collection in this study was carried out using a structured research questionnaire to 68 PLTH electricity beneficiaries in Pantai Baru, where they are also managers of tourism business in Pantai Baru.This study uses a frequency distribution analysis method to identify: (1) the profile of renewable electricity beneficiaries and (2) determine the extent of empowerment renewable energy electricity beneficiaries in Pantai Baru. The results showed that the characteristics of the beneficiaries were generally of a mature age, had a clear direction of life and goals, and had and adequate level of education. Furthermore, in terms of the empowerment indicators used in this study, they are rated as high. Thus, this study indicates that the community empowerment activities through the development of renewable energy have an impact to the empowerment of PLTH electricity beneficiaries in Pantai Baru.